Navigating Rubber Band Syndrome in Dogs: A Report of Three Cases - Reddy, Puli Vishnu Vardhan; Raj, Pushkin; Simon, Shiju; Sindhu, Ramasamy; Ratnam, Thenmozhi (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The presence of strangulating foreign bodies within the limbs of dogs is a matter of considerable veterinary concern due to the potential for various complications, including constriction, compromised blood flow, and damage to musculoskeletal and neurovascular structures (John et al., 2019). A specific manifestation of this issue is rubber band syndrome or circumferential strangulating foreign bodies, characterized by the presence of encircling external materials around distal limbs (Arora and Agarwal, 2004; Aggarwal et al., 2010). Notably, this phenomenon is predominantly reported in India, where ceremonial or religious bands, often worn for both aesthetic and ritualistic purposes, are frequently tied around wrists and ankles. Unfortunately, these bands are inadvertently forgotten, resulting in adverse consequences (Baddula et al., 2021).